2004
DOI: 10.1080/10408690490489224
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Biological, and Evolutionary Relationships of Plant Food Allergens Sensitizing via the Gastrointestinal Tract

Abstract: The recently completed genome sequence of the model plant species Arabidopsis has been estimated to encode over 25,000 proteins, which, on the basis of their function, can be classified into structural and metabolic (the vast majority of plant proteins), protective proteins, which defend a plant against invasion by pathogens or feeding by pests, and storage proteins, which proved a nutrient store to support germination in seeds. It is now clear that almost all plant food allergens are either protective or stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
0
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(144 citation statements)
references
References 205 publications
1
133
0
10
Order By: Relevance
“…However, one of the hypotheses has been that for a protein to be a food allergen, it must survive the digestion process through the gastrointestinal tract, to reach the immune system as an intact protein or as large peptide fragments. 1,2 The first systematic assessment of food allergen digestibility was conducted in 1996 by Astwood et al 3 They showed that in general food allergens were resistant to pepsin digestion, whereas nonallergenic proteins were more easily digested. Since this, several studies examining the correlation between resistance to digestion and allergenicity have been made, where the correlation between stability and allergenicity was less clear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, one of the hypotheses has been that for a protein to be a food allergen, it must survive the digestion process through the gastrointestinal tract, to reach the immune system as an intact protein or as large peptide fragments. 1,2 The first systematic assessment of food allergen digestibility was conducted in 1996 by Astwood et al 3 They showed that in general food allergens were resistant to pepsin digestion, whereas nonallergenic proteins were more easily digested. Since this, several studies examining the correlation between resistance to digestion and allergenicity have been made, where the correlation between stability and allergenicity was less clear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…NsLTPs were identified as major allergens in fruits and in many other plant foods causing severe allergenic symptoms (Zuidmeer & van Ree, 2007). Recently published reviews have provided a thorough background on nsLTPs in foods and pollen (Mills et al, 2004;Salcedo et al, 2004Salcedo et al, , 2007Breiteneder & Mills, 2005). Major allergens of Parietaria judaica L. pollen grains, Par j 1 and Par 2, belong to the nsLTP family (Costa et al, 1994;Asturias et al, 2003; (1).…”
mentioning
confidence: 99%
“…The main components of the globulin fraction are globulin 11S -legumin and globulin 7S -vicilin [Lampart-Szczapa 2001, Kędzior 2004. The sequence and structure of pea legumin are similar to those noted in soybean legumin [Mills et al 2004]. Legumin is composed of an α-chain with molecular weight of approximately 40 kDa, which contains signifi cant quantities of acidic amino acids, and a β--chain with molecular weight of approximately 20 kDa, which contains basic amino acids.…”
Section: Introductionmentioning
confidence: 76%
“…The amino acid sequences of vicilin listed in the UniProtKB database are nearly completely devoid of tryptophan, and they can be differentiated from other pea proteins based on their derivative UV absorption spectra [Minkiewicz et al 2006]. Albumin proteins of legumes, including pea, have been less extensively researched than globulins [Mills et al 2004, Kędzior 2004. This fraction comprises proteins with molecular weight of 6 to 100 kDa, including enzymes, enzyme inhibitors and lectins.…”
Section: Introductionmentioning
confidence: 99%